On the nature of social interactions and cognition in learning communities - Oztok, Murat (Proceedings of the International Conference on Networked Learning, 2024)
Whether explicitly used as a research aim or implicitly discussed as an outcome, the concept of community is central for the networked learning research as it allows networked learning researchers to study how people perceive the networked environment as a space, wherein the members can develop relationships among one another. The underlying premise for this work is that it is erroneous to assume a learning community is a unified concept, functioning in the same way for everyone under same circumstances. Taking the contextual factors into account, this research questions the characteristics of a community that are related to learning. I explore how different types of relationships among members of a learning community are related to learning. In particular, I conceptualise the concept of community using social capital theory. Since the central tenet of social capital theory is that different relationships within networks of people hold different values, I argue that it can inform the ways by which the perceived level of learning is understood with respect to interaction patterns. The findings suggest that both distributed–diverse communications and strong–close communications are manifest in learning. However, the impact of diverse relationships on learning is considerably larger and stronger compared to denser relationships. The implications are discussed.